QOL-33. FERTILITY PRESERVATION IN GIRLS WITH BRAIN TUMORS: A SINGLE CENTER EXPERIENCE. Issue 2 (22nd June 2018) - Dvir, Rina; Azem, Foad; Manistersky, Michal; Berkley, Ilana; Elhasid, Ronit
Abstract: INTRODUCTION: Premature ovarian dysfunction is increasingly documented in survivors of brain tumors particularly in girls who received high doses of radiotherapy and alkylating agents. Fertility preservation in girls is an important procedure which should be offered to patients with increased risk of gonadal failure. Risk groups for ovarian dysfunction have been previously documented (i.e. Edinburgh criteria). Our center provides a fertility counsel for all girls with pediatric cancer, and patients at increased risk are offered ovarian cryopreservation. PATIENTS AND METHODS: A retrospective analysis of girls treated with brain tumors between 2010-2016 was performed. We documented age, disease type, treatment protocols, preservation treatment details, treatment delay and complications. RESULTS: 41 girls with brain tumors were assessed. Eight underwent laparoscopic ovarian cryopreservation (6 medulloblastoma, 2 pineal tumors, age range 8-18 years, median 10.4 years). Five had insertion of portacath in the same operative session. Two girls had a prior V-P shunt. Fertility preservation was not performed in: 11 girls with high grade glioma, 4 metastatic tumors, 7 low grade glioma, 4 craniopharyngioma, 3 younger than 3 years and parental refusal in 4. Cryopreservation caused no complications or delays in treatment. CONCLUSIONS: Ovarian cryopreservation is recommended when there is a high risk of gonadal failure from oncologic treatment. Fertility counseling by a specialized clinic provides individualized recommendations. Ovarian cryopreservation can be safely performed in selected cases without complications even concurrently with central line insertion, or after V-P shunting. Current knowledge regarding future uses of cryopreserved tissue shall be discussed.